120 W Greenlight HPS Laser Photoselective Vaporization of the Prostate for Treatment of Benign Prostatic Hyperplasia in Men with Detrusor Underactivity - Choi, Sae Woong (The Korean Urological Association, 2011)
PURPOSE: Most men with benign prostatic hyperplasia (BPH) have bothersome lower urinary tract symptoms (LUTS). This study aimed to investigate the safety and efficacy of high-performance system (HPS) laser photoselective vaporization of the prostate (PVP) for the treatment of BPH in men with detrusor underactivity (DU). MATERIALS AND METHODS: From March 2009, 371 patients with BPH were divided into 2 groups according to the findings of preoperative urodynamic study: 239 (64.4%) patients with bladder outlet obstruction (BOO) and 132 (35.6%) patients with bladder outlet obstruction with detrusor underactivity (BOO+DU). 120 W HPS laser PVP was performed to resolve the BOO. The perioperative data and postoperative results at 1 month and 12 months, including the International Prostate Symptom Score (IPSS), maximum urinary flow (Qmax), and postvoid residual urine (PVR) values, were evaluated. RESULTS: Compared with the preoperative parameters, significant improvements in IPSS, Qmax, and PVR were observed in each group at 1 and 12 months after the operation. In addition, IPSS, Qmax, and PVR were not significantly different between the BOO and BOO+DU groups at 1 and 12 months after the operation. CONCLUSIONS: Surgery to relieve BOO in the patients with BPH seems to be an appropriate treatment modality regardless of the existence of DU.